Ginkgolide B improves multiterritory perforator flap survival by inhibiting endoplasmic reticulum stress and oxidative stress. Issue 6 (3rd July 2021) - Lin, Damu; Wu, Hongqiang; Zhou, Zongwei; Tao, Zhenyu; Jia, Tanghong; Gao, Weiyang
Abstract: Background: The therapeutics used to promote perforator flap survival function induces vascular regeneration and inhibit apoptosis. The present study aimed to explore the potential mechanism of the angiogenesis effects of Ginkgolide B (GB) in perforator flaps. Methods: A total of 72 rats were divided into three groups and treated with saline, GB, or GB + tunicamycin (TM; ER stress activator) for seven consecutive days, respectively. Apoptosis was assayed by determining the Bax/Bcl-2 ratio and caspase-3 level. Endoplasmic reticulum (ER) stress markers (CHOP, GRP78, and caspase-12) were detected by Western blot analysis. Oxidative stress was assessed by measuring the superoxide dismutase activity (SOD) and malondialdehyde (MDA), heme oxygenase-1(HO-1), and nuclear factor erythroid-2-related factor 2 (Nrf2) mRNA levels in the flaps. The percentage flap survival area and blood flow were assessed on postoperative day (POD) 7. Angiogenesis was visualized by hematoxylin and eosin and CD34 staining on POD 7. Results: GB increased the survival of perforator flaps, the flap survival area of GB, GB + TM, and control groups was 90.83 ± 1.93%, 70.93 ± 4.13%, and 62.97 ± 6.50%. GB decreased the Bax/Bcl-2 ratio and caspase-3 level. ER stress-related proteins were downregulated by GB. GB also decreased the MDA level and increased SOD activity, HO-1 and Nrf2 mRNA levels in the flaps. Further, GB induced regeneration of vascular vessels in comparison with saline or GB + TM. Conclusions: GB increased angiogenesis and alleviated oxidative stress by inhibiting ER stress, which increased the survival of perforator flaps. In contrast, GB + TM alleviated angiogenesis and induced oxidative stress by activating ER stress and decreasing the survival of perforator flaps.